Strategies for the Development of Jamu Events (Modern Jamu Era) in the Gen Z Era in the Old City - Florensia Lavenia (Green Publisher Indonesia, 2025)
Jamu is a traditional Indonesian herbal drink made from natural ingredients such as spices and leaves. According to Permenkes No. 003/Menkes/Per/I/2010, herbal medicine consists of plant, animal, or mineral ingredients, or their mixtures, used for treatment based on traditional experience and societal norms. This research aims to preserve Indonesia's cultural heritage, specifically Indonesian herbal medicine, and to develop the introduction of its history and stories. Using a qualitative research method, the data collection techniques employed were interviews, observations, and documentation, while data analysis was conducted through a descriptive qualitative approach. The conclusions of this research highlight the strategies for the development of jamu events (modern jamu era) in the Gen Z era in the old city employed by Acaraki Cafe, namely: maintaining and adding programs to introduce herbal medicine alongside technological advancements; increasing the use of technology to collaborate with modern beverage brands; and maintaining and promoting honey-mixed beverages through social media. The suggestion and recommendation from the researcher is to create workshops that invite school children and students to learn about the history and benefits of herbal medicine and jamu.